Student Learning Independence : Antecedents and Consequences - S, Fitriani.; Bado, Basri; Inanna; Supatminingsi, Tuti; Najamuddin (MultiTech Publisher, 2024)
This study aims to examine and analyze the antecedents and coznsequences of student learning independence after the Covid-19 pandemic in economics subjects. The antecedents of independent learning in this study are self-efficacy, motivation to learn, and the environment while the consequences of independent learning in this study are learning achievement and critical thinking skills. This research is a quantitative research with path analysis data analysis techniques. The research results show that; 1) Self-efficacy, learning motivation and environment have a positive and significant effect on learning independence. 2) Self-efficacy has a direct, significant positive effect on learning achievement and critical thinking skills, while learning motivation directly has a non-significant negative effect on learning achievement, but a significant positive effect on critical thinking skills and the environment has a direct, insignificant negative effect on learning achievement and thinking ability critical. 3) Learning independence has a positive and significant effect on learning achievement and critical thinking skills. 4) Self-efficacy, learning motivation and environment indirectly have a significant effect on learning achievement and critical thinking skills through independent learning